Case Report: Are You One of Us and Can We Trust You?: Taking a Communication Perspective in Participatory Research - Fisher-Yoshida, Beth (Frontiers in Communication, 2021)
This article focuses on the necessity to build relationships with people across cultures, while doing participatory action research (PAR). There are many assumptions attached to the term “participation” and it is not only worth exploring how these assumptions are formed and how they manifest during participatory action research projects, but is necessary to build trusting relationships. Taking a communication perspective through the lens of Coordinated Management of Meaning (CMM), provides the framework to see which voices are heard and privileged, and how researchers with more formal experience blend in partnership with those possessing local knowledge and practices. These many influences shape the dynamics of the relationships, create the episodes of which these experiences are a part, and impact the efficacy of the work. These layers of complexity need to be considered and addressed. CMM Models and concepts aid us in becoming aware of the moral or “logical” forces that are attached to the contexts we prioritize and was applicable to the case study we did in Medellín, Colombia, which was key to developing self-awareness. These contextual influences are culturally bound and in order to have equitable participatory processes across cultures, becoming more aware of the origin of these tendencies is critical. In addition, the more self-aware all the researchers become, the more it leads to developing better partnerships in these PAR processes.